SARS-CoV-2 infection and human semen: possible modes of contamination and transmission - Bhattacharya, Koushik; Mukhopadhyay, Lipika Das; Goswami, Ratnadeep; Dutta, Sulagna; Sengupta, Pallav; Irez, Tulay; Abdul Hamid, Habibah; Syamal, Alak Kumar (SpringerOpen, 2021)
Background: Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), has turned into a global pandemic with multitudinous health impacts. Main body: In light of the higher vulnerability of men to COVID-19 than women, there is rising concerns on the impact of SARS-CoV-2 infection on male fertility and possibilities of seminal contamination and transmission. The pandemic has attributed to the brief suspension of many fertility clinics and pathology laboratories, though many remained functional. Few reports reflect that SARS-CoV-2 can contaminate the semen of COVID-19 patients as well as that of recovering patients. The viral invasion into the testis may be due to the disrupted anatomical barriers of the testis by the inflammatory responses, and the persistence of the virus in the semen may be facilitated by the testicular immune privilege. Since SARS-CoV-2 is an enveloped RNA virus, it is also theoretically possible that this virus can remain viable in the semen samples even after cryopreservation with liquid nitrogen. Conclusion: The present review emphasizes the possibilities of seminal dissemination of SARS-CoV-2 and thereby the chances of its sexual transmission. These perceptions and predictions are to facilitate immediate necessary actions to improvise the standard precautionary procedures for laboratory practices, including semen analysis or processing the semen sample for fertility treatments.